Cynipidae (Hymenoptera: Cynipoidea) on Cyclobalanopsis (Fagaceae) in Mainland China, with the First Record of Sexual Generation of Cynipini in Winter. (12th January 2015) - Abe, Yoshihisa; Ide, Tatsuya; Odagiri, Ken-Ichi
Abstract : Cycloneuroterus wangi Abe, Ide, & Odagiri sp. nov. and Dryocosmus nanlingensis Abe, Ide, & Odagiri sp. nov. are described from Mainland China. Gall wasps associated with Quercus ( Cyclobalanopsis ) sessilifolia Blume, which is distributed in Japan, Taiwan, and Mainland China, have not yet been recorded. However, this evergreen oak species is considered to be the host plant of C. wangi on the basis of an observation in which eight females of this gall wasp species inserted their ovipositors into the buds of Q . ( C .) sessilifolia . This is the first record of the Cynipidae (Hymenoptera: Cynipoidea) being associated with Cyclobalanopsis from Mainland China. As cynipids associated with Cyclobalanopsis have previously been known from Japan, Taiwan, and Vietnam, the discovery of C. wangi indicates that oak gall wasps associated with Cyclobalanopsis are widely distributed in Asia, as predicted previously. The collection of an adult male of D. nanlingensis by sweeping Fagaceae trees represents the first observation of a sexual generation of Cynipini in winter. Further investigations are necessary to elucidate the life cycle and to identify the host plant of D. nanlingensis . Cynipid species richness in broadleaf forests dominated by Fagaceae is considered to be high in Mainland China because of remarkable diversity of potential host plants, such as oaks and related taxa.